2023
DOI: 10.1371/journal.pone.0290638
|View full text |Cite
|
Sign up to set email alerts
|

Practices and motives behind antibiotics provision in drug outlets in Tanzania: A qualitative study

Pendo M. Ndaki,
Joseph R. Mwanga,
Martha F. Mushi
et al.

Abstract: Dispensing antibiotics without prescription is among the major factors leading to antimicrobial resistance. Dispensing of antibiotics without prescription has negative impact at the individual and societal level leading to poor patient outcomes, and increased risks of resistant bacteria facilitated by inappropriate choice of antibiotics doses/courses. Antimicrobial resistance is a global public health threat which is projected to cause 10 million deaths by 2050 if no significant actions are taken to address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, there have been increasing concerns regarding the irrational prescribing of antibiotics among healthcare professionals (HCPs) in Tanzania, including for the management of diarrhea and respiratory illnesses in children, enhancing AMR [59][60][61][62][63]. AMR is further exacerbated in Tanzania by antibiotics being widely available and used without a prescription (Table S2) [59,[64][65][66][67][68][69], enhanced by issues of affordability and convenience [59]. For instance, in their study among 59 LMICs, Hossain et al (2023) found that only 22.4% of children in Tanzania with either a cough or fever received antibiotics from qualified sources, e.g., recognized hospitals and clinics [70].…”
Section: Schmeider Et Al 2022 [51]mentioning
confidence: 99%
“…In addition, there have been increasing concerns regarding the irrational prescribing of antibiotics among healthcare professionals (HCPs) in Tanzania, including for the management of diarrhea and respiratory illnesses in children, enhancing AMR [59][60][61][62][63]. AMR is further exacerbated in Tanzania by antibiotics being widely available and used without a prescription (Table S2) [59,[64][65][66][67][68][69], enhanced by issues of affordability and convenience [59]. For instance, in their study among 59 LMICs, Hossain et al (2023) found that only 22.4% of children in Tanzania with either a cough or fever received antibiotics from qualified sources, e.g., recognized hospitals and clinics [70].…”
Section: Schmeider Et Al 2022 [51]mentioning
confidence: 99%